Konfigurasi Modul Inventori, Penjualan, Pembelian dan Manufaktur dengan Odoo pada UKM MPC - Nikolas Pradipto (UNIVERSITAS KALBIS, 2022)
MPC is a small-medium business that selling food and beverage. MPC have 4 stores with 1 store is the headquarter that selling big orders and the other 3 is a branch that selling smaller sales. MPC doesn’t prepared to be as big as now so they don’t have a system that can handle inventories. Another process such as procurement, storing product, and sales is running manually. This research has a goal to create a integrate system that can connecting between headquarter and the branches with their resources so they can manage the inventories together. The integrated system for this research will be using Odoo 12 implemented by ASAP method. This research will give you Odoo database that configurated with the business will needs